SWIFT de-magnifying image slicer: Diffraction limited image slicing at optical wavelengths - Tecza, M; Thatte, N; Clarke, F; Fogarty, L; Goodsall, T; Salter, G; Freeman, D; Salaun, Y (2008)
We present the manufacturing and first results from testing and characterising the SWIFT image slicer. The SWIFT image slicer design is based on the MPE-3D and SPIFFI image slicers. It uses plane mirrors to slice the input field but through a novel, de-magnifying design, using a mosaic of spherical lenses, it achieves a considerable de-magnification. Classical polishing techniques can be applied to manufacture both plane and spherical surfaces with very high surface accuracy and quality reducing aberrations and scattered light. The SWIFT image slicer was manufactured over a 18 months period and was delivered to Oxford in September 2007. The commissioning of the SWIFT instrument will take place in August/September 2008.